(3GdeSGFd aj GdRgOs - (3CHh YHO Gddg GdMGQK Hf CSO GdeMGSHj, GdMGQK GdeMGSHj,J (B243 (3g` s
(3ChdgG (B:s
(3SFd GHh YHO Gddg GdMGQK Hf GSO Hf YHO Gddg GdeMGSHi QMeg Gddg Yf GdRgO ai GdOfjG GaQV Ge fbd s
(3BNQgG (B:s
(3haQV Ydjge ai fbdge cja jCNPhf hjJQchf BNQ cJGH GdeSGFd s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3JdjI aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B517s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs